Phenolic Composition and Antioxidant Activity of Malus domestica Leaves. (11th September 2014) - Liaudanskas, Mindaugas; Viškelis, Pranas; Raudonis, Raimondas; Kviklys, Darius; Uselis, Norbertas; Janulis, Valdimaras
Abstract : The aim of this study was to determine the composition and content of phenolic compounds in the ethanol extracts of apple leaves and to evaluate the antioxidant activity of these extracts. The total phenolic content was determined spectrophotometrically, as well as the total flavonoid content in the ethanol extracts of apple leaves and the antioxidant activity of these extracts, by the ABTS, DPPH, and FRAP assays. The highest amount of phenolic compounds and flavonoids as well as the highest antioxidant activity was determined in the ethanol extracts obtained from the apple leaves of the cv. Aldas. The analysis by the HPLC method revealed that phloridzin was a predominant component in the ethanol extracts of the apple leaves of all cultivars investigated. The following quercetin glycosides were identified and quantified in the ethanol extracts of apple leaves: hyperoside, isoquercitrin, avicularin, rutin, and quercitrin. Quercitrin was the major compound among quercetin glycosides.